Business or fun? : similarities and differences between Portuguese and International wine bloggers - Santos, J. Freitas (2012)
The worldwide emergence of blogs has presented marketers with a new communication channel. Despite the increasing growth of wine blogs little is understood about the practices and motivations of wine bloggers. This exploratory study investigates the similarities and differences of profile, uses and motivations between Portuguese and international wine bloggers. The results show significant differences in rating (rating versus non-rating) and wine samples (acceptance or not). Marginally differences were found in the blogging activity age and motivations. Similarities were found in the frequency of posts, adoption of advertising, statistical tools to measure blog traffic and licence content of the blog